2019
DOI: 10.4317/jced.55814
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of 102 patients with oral lichen planus in Thailand

Abstract: Background: Oral lichen planus (OLP) is a chronic inflammatory disease of the skin and mucous membrane presented with various clinical appearances. The aim of the present study was to elucidate the clinical profile of patients with OLP. Material and Methods: The dental records of 102 patients who visited Oral Medicine Clinic, Dental Hospital, Naresuan University during 2002-2018 were retrospectively reviewed. Results: There were 75 (73.5%) women and 27 (26.5%) men, giving a female to male ratio of 2.8:1. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…As regards localization related to the OHRQoL, the OLP lesions most frequently involved were on the buccal mucosa followed by the gingiva, tongue and lip, while the involvement of the hard palate, floor of the mouth and soft palate were rarely affected. These results are in accordance with previously published studies [ 1 , 3 , 53 ]. Osipoff et al [ 48 ] found that OLP of the tongue was the most painful lesion, which differed from our results that showed no difference in the pain perception with respect to the location.…”
Section: Discussionsupporting
confidence: 94%
“…As regards localization related to the OHRQoL, the OLP lesions most frequently involved were on the buccal mucosa followed by the gingiva, tongue and lip, while the involvement of the hard palate, floor of the mouth and soft palate were rarely affected. These results are in accordance with previously published studies [ 1 , 3 , 53 ]. Osipoff et al [ 48 ] found that OLP of the tongue was the most painful lesion, which differed from our results that showed no difference in the pain perception with respect to the location.…”
Section: Discussionsupporting
confidence: 94%
“…The lesions were mainly symptomatic (92.2%) and involved multiple locations (67.6%) where the buccal mucosa (79.4%) were primarily affected. (Kaomongkolgit et al, 2019) (Muthukrishnan, Kumar and Ramalingam, 2016) Based on our study, the prevalence of recurrence of oral lichen planus was 54.2% in total of males and females with the prevalence of OLP among males being 50% and among females being 62.5% respectively. In both aspects, females have a higher prevalence of cases than males in both primary and recurrent oral lichen planus as seen in the study conducted by Kaomongkolit et al (Subashri and Uma Maheshwari, 2016;Kaomongkolgit et al, 2019) In the case of clinical variants of oral lichen planus, primary oral lichen planus have variants that can be divided into erosive, reticular and bullous while in recurrent oral lichen planus, the clinical variants are divided into erosive, reticular, papular, pigmented and ulcerative forms of oral lichen planus, this can be supported by the study Jo Andressan, which elaborated about a clinical examination of 115 cases of oral lichen planus has been presented.…”
Section: Resultsmentioning
confidence: 64%
“…It leads to the severe destruction of the epithelial basal layer 2 . Oral lichen planus usually presents bilaterally on mucosae of inner cheeks and has various clinical patterns; with reticular, erythematous (erosive), plaque and ulcerative being the most common 5,6 . These patterns may coexist in the same region or may alternate in time 6 .…”
Section: Discussionmentioning
confidence: 99%
“…These patterns may coexist in the same region or may alternate in time 6 . The most commonly affected sites are the buccal mucosa, the tongue and the gingiva 4,5 . Involvement of the palate and lips is rare, and even rarer is the involvement of the oral floor 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation